2018
DOI: 10.1145/3274356
|View full text |Cite
|
Sign up to set email alerts
|

'It's More Like a Letter'

Abstract: Communication technologies for maintaining close personal relationships are often designed to be lightweight and easy to use. While these properties allow for relationships to be maintained with speed and efficiency, they may come at the expense of more effortful messages that are constructed with thought, time and care. This raises the question of how communication technologies might be designed to provoke moments of effortful maintenance from their users. To explore this question, we designed and implemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…In the first cycle, the participants took part in a series of workshops that were designed to familiarise them with VR and the use of avatars. This culminated in a workshop where they trialled a basic social VR prototype that allowed them to control embodied avatars via a Microsoft Kinect sensor [3]. In the second cycle, a subset of the same group of participants were involved in the participatory design of a social VR application concept [5] that was used as the basis for the prototype that was developed for the user study [2].…”
Section: Participatory Methodology and Contextmentioning
confidence: 99%
See 4 more Smart Citations
“…In the first cycle, the participants took part in a series of workshops that were designed to familiarise them with VR and the use of avatars. This culminated in a workshop where they trialled a basic social VR prototype that allowed them to control embodied avatars via a Microsoft Kinect sensor [3]. In the second cycle, a subset of the same group of participants were involved in the participatory design of a social VR application concept [5] that was used as the basis for the prototype that was developed for the user study [2].…”
Section: Participatory Methodology and Contextmentioning
confidence: 99%
“…We are aware of only one study that has considered AMC in social VR. Baker and colleagues [3] report on a study that saw 25 older adults aged between 70 and 81 engage in a social VR prototype that allowed groups of four people to visit a virtual island and engage in conversation. Results from this study showed that while the participants saw great potential for AMC in social VR to be used as a tool to address social isolation, several factors impacted on their ability to feel socially engaged during the study.…”
Section: Amc In Social Virtual Worlds and Social Vr By Older Adultsmentioning
confidence: 99%
See 3 more Smart Citations